A methodology for modelling energy use in the agriculture sector for the Pakistan integrated energy model. (2015) - Irfan, Sayed M.
This paper attempts to rationalise and facilitate the application of the MARKAL/TIMES modelling framework for modelling and planning energy use in Pakistan which has been developed as the Pakistan integrated energy model (Pak-IEM) by the Government of Pakistan. The arguments are developed by applying the paradigm to the agriculture sector. This modeling approach is rooted in the fundamentals of decision modelling involving the explicit identification of values and objectives, the decision context, and the use of a logical framework to structure the elements of the decision situation through influence diagrams. This lends itself perfectly to a linear programming modelling framework. The practical implications of this are the advantages to be gained in successive refinements of the integrated model in later years, contingent to operational, policy, or technology changes. This capability, hopefully, will identify a host of potentially feasible related projects that can be undertaken within various sectors.